High prevalence of deleterious mutations in concomitant nonsyndromic cleft and outflow tract heart defects. Issue 7 (6th April 2022) - Munabi, Naikhoba C. O.; Mikhail, Shady; Toubat, Omar; Webb, Michelle; Auslander, Allyn; Sanchez‐Lara, Pedro A.; Manojlovic, Zarko; Schmidt, Ryan J.; Craig, David; Magee, William P.; Kumar, Subramanyan Ram
Abstract: Our previous work demonstrating enrichment of outflow tract (OFT) congenital heart disease (CHD) in children with cleft lip and/or palate (CL/P) suggests derangements in common underlying developmental pathways. The current pilot study examines the underlying genetics of concomitant nonsyndromic CL/P and OFT CHD phenotype. Of 575 patients who underwent CL/P surgery at Children's Hospital Los Angeles, seven with OFT CHD, negative chromosomal microarray analysis, and no recognizable syndromic association were recruited with their parents (as available). Whole genome sequencing of blood samples paired with whole‐blood‐based RNA sequencing for probands was performed. A pathogenic or potentially pathogenic variant was identified in 6/7 (85.7%) probands. A total of seven candidate genes were mutated ( CHD7, SMARCA4, MED12, APOB, RNF213, SETX, and JAG1 ). Gene ontology analysis of variants predicted involvement in binding (100%), regulation of transcription (42.9%), and helicase activity (42.9%). Four patients (57.1%) expressed gene variants ( CHD7, SMARCA4, MED12, and RNF213 ) previously involved in the Wnt signaling pathway. Our pilot analysis of a small cohort of patients with combined CL/P and OFT CHD phenotype suggests a potentially significant prevalence of deleterious mutations. In our cohort, an overrepresentation of mutations in molecules associated with Wnt‐signaling was found. These variants may represent an expanded phenotypic heterogeneity within known monogenic disease genes or provide novel evidence of shared developmental pathways. The mechanistic implications of these mutations and subsequent developmental derangements resulting in the CL/P and OFT CHD phenotype require further analysis in a larger cohort of patients.